PEMBIASAAN PERILAKU SOPAN SANTUN DALAM UPAYA MENINGKATKAN KARAKTER ISLAMI SANTRI DI PONDOK PESANTREN - Makhmudah, Siti (ABDI MASYARAKAT, 2025)
Islamic boarding schools are very important in playing a role in instilling good morals. And it is hoped that Islamic boarding schools will become a place of social reliability of morals that must be given to students. Although Islamic boarding schools are still lacking in instilling morals, therefore the program "implementation of polite habits to improve Islamic character" was implemented at the Al Huda Bogo Nganjuk Islamic Boarding School. The purpose of this program is to improve Islamic character in having good morals in everyday life. In collecting data, researchers conducted observations, interviews and discussions and analyzed morals in students at Islamic boarding schools, using the ABCD asset multiplication method. In this activity, researchers involved administrators and new students. The target of the activity is that all new students start from the introduction of polite morals at the boarding school through the program. The results obtained in instilling morals of students are categorized as quite successful.